Penyelenggaraan Kursus BEC (Basic English Course) Berbasis Oligopoli dalam Meningkatkan Pendapatan Warga Masyarakat RT 02 RW XII Dusun Singgahan Desa Selodono Kecamatan Ringinrejo Kabupaten Kediri - AHMAD AFANDI (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan UNESA, 2016)
ABSTRACT IMPLEMENTING OLIGOPOLY BASE BEC (BASIC ENGLISH COURSE) IN IMPROVING INCOME OF RT 02 RW XII DUSUN SINGGAHAN DESA PELEM KECAMATAN PARE KABUPATEN KEDIRI SOCIETY Name : Ahmad Afandi Register number : 12010034046 Study Program : S-1 Major : Non Formal Education Faculty : Faculty of Education Institution : State University of Surabaya Advisor : Dr. Hj. Gunarti Dwi Lestari, M.Si, M.Pd Course is the unit of non formal education which provides many kinds of knowledge, skills, mental behaviors for studying society in teaching learning process as well as formal school. The different is that course is held to be done in short term and to study one certain skill in order to reach self-development, to earn living, to continue to higher education. BEC (Basic English Course) institution is one of courses who implements English course for 6 months in order to maximize English competency of studying society. In its implementation, BEC (Basic English Course) used Oligopoly system. Oligopoly is a marketing in which the form of competition is dominated by 2 or more producers/consumers in each different characteristic area. By applying Oligopoly system, society is given opportunities to participate for fulfilling needs of studying society in establishing new service base business. The Approach used in this research was qualitative. The data were collected by in-depth interview, observation and documentation. Data analyses used in this research were data collection, data reduction, data presentation and data verification. Results of this research showed that the implementing Oligopoly base BEC (Basic English Course) in improving income of society ran properly due to the indicators and purposes of the owner of BEC (Basic English Course) in fulfilling needs of studying society. It was proven that Oligopoly system affected to the ability of society in establishing new service base business in order to fulfill needs of studying society from BEC (Basic English Course). Concrete proofs from society’s capability to establish new service base business in order to fulfill needs of studying society from BEC (Basic English Course) was that the owner of BEC (Basic English Course) not only established course institution but also participated in establishing boarding house, restaurant, cycling rental, and laundry. From establishing new business, society’s income was improved than before. Keywords: Course Implementation, Oligopoly, Income ABSTRAK PENYELENGGARAAN KURSUS BEC (BASIC ENGLISH COURSE) BERBASIS OLIGOPOLI DALAM MENINGKATKAN PENDAPATAN WARGA MASYARAKAT RT 02 RW XII DUSUN SINGGAHAN DESA PELEM KECAMATAN PARE KABUPATEN KEDIRI Nama : Ahmad Afandi NIM : 12010034046 Program Studi : S1 Jurusan : Pendidikan Luar Sekolah Fakultas : Ilmu Pendidikan Nama Lembaga : Universitas Negeri Surabaya Dosen Pembimbing : Dr. Hj. Gunarti Dwi Lestari, M.Si, M.Pd Kursus merupakan satuan pendidikan luar sekolah yang menyediakan berbagai jenis pengetahuan, keterampilan, dan sikap mental bagi warga belajar dalam kegiatan belajar mengajar seperti halnya sekolah formal. Perbedaannya adalah bahwa kursus diselenggarakan dalam waktu pendek dan hanya mempelajari satu keterampilan tertentu dengan tujuan untuk mengembangkan diri, bekerja mencari nafkah dan melanjutkan pendidikannya ke jenjang yang lebih tinggi. Lembaga kursus BEC (Basic English Course) adalah salah satu contoh lembaga kursus yang menyelenggarakan kursus bahasa Inggris selama 6 bulan dengan tujuan untuk memaksimalkan kemampuan bahasa Inggris warga belajar. Dalam penyelenggaraannya BEC (Basic English Course) menggunakan sistem Oligopoli. Oligopoli merupakan suatu pasar dimana bentuk persaingan didominasi oleh lebih dari 2 produsen atau penjual dalam suatu area yang memiliki karakteristik tersendiri. Dengan sistem oligopoli tersebut masyarakat diberi kesempatan untuk berpartisipasi dalam memenuhi kebutuhan warga belajar, yaitu dengan mendirikan usaha baru dibidang jasa. Pendekatan dan jenis penelitian yang digunakan adalah kualitatif. Data dikumpulkan dengan teknik wawancara mendalam, observasi dan dokumentasi. Analisis data yang digunakan adalah koleksi data, reduksi data, penyajian data dan verifikasi data. Hasil penelitian menunjukkan bahwa penyelenggaraan kursus BEC (Basic English Course) berbasis oligopoli dalam meningkatkan pendapatan warga masyarakat berjalan sesuai indikator dan tujuan pengelola mendirikan lembaga kursus BEC (Basic English Course). Terbukti bahwa sistem oligopoli berdampak pada mampunya warga masyarakat mendirikan usaha baru dibidang jasa dengan tujuan untuk memenuhi kebututuhan warga belajar dari BEC (Basic English Course). Kata Kunci : Penyelenggaraan kursus, sistem oligopoli, pendapatan